Morphological Patterns of Anaemia and Prevalence of Haemoglobinopathy in State of Haryana: Study from a Tertiary Hospital - Singh, Sonia; Sen, Rajiv; Singh, Sunita; Pawar, Richa; Malik, Shivani; Langan, Rinky (Annals of Pathology and Laboratory Medicine, 2018)
Background: Hemoglobinopathies including thalassemias are important prevalent group of erythrocytic genetic disorders found in various parts of the world and are important cause of morbidity and mortality. Methods: Samples were run on 5 part differential cell counter and after analyzing various RBC parameters and peripheral smear, the appropriate sample on biorad HPLC for hemoglobinopathy and mutation study was done. Statistical analysis performed. Study population included two groups- anemic pregnant women and students. Result: Out of 361 cases; 27 were positive for haemoglobinopathies giving a prevalence of 7.5 % in anemic mothers. Positive cases included 22 cases of Î²-thalassemia trait, 2 HbS trait, 1 case of HbD trait, 1 case of HbE trait and 1 case of HbE homozygous. Out of a total of 630 cases, 38 were found positive for various haemoglobinopathies including 36 cases of Î²-thalassemia trait, 1 case of thalassemia intermedia and 1 case of HbLepore. DNA analysis was done for 10 cases in which the common mutation found was IVSI-5 followed by codon 41/42 and codon 8/9 Conclusion: Proper screening studies should be done to diagnose the cases and reduce the prevalence of thalassemia major by informing and educating such cases.